2016
DOI: 10.3847/0004-637x/822/2/97
|View full text |Cite
|
Sign up to set email alerts
|

ROTATION–ACTIVITY CORRELATIONS IN K AND M DWARFS. I. STELLAR PARAMETERS AND COMPILATIONS OF v sin i AND P/sin i FOR A LARGE SAMPLE OF LATE-K AND M DWARFS*

Abstract: The reliable determination of rotation-activity correlations (RACs) depends on precise measurements of the following stellar parameters: T eff , parallax, radius, metallicity, and rotational speed vsini. In this paper, our goal is to focus on the determination of these parameters for a sample of K and M dwarfs. In a future paper (Paper II), we will combine our rotational data with activity data in order to construct RACs. Here, we report on a determination of effective temperatures based on the (R-I) C color… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 91 publications
9
31
1
Order By: Relevance
“…We find good agreement between our SPECMATCH-EMP derived stellar parameters from the PFS template spectrum and those derived by Niraula et al (2017) and by Houdebine et al (2016) as reported in Rodriguez et al (2017). Our T eff and log g values for GJ 9827 are slightly lower (4085±70 K versus their 4255±110 K and 4270±100 K, 4.67±0.12 cgs versus their 4.70±0.15 cgs and 4.9±0.2 cgs), and our metallicity is Neither Niraula et al (2017) nor Rodriguez et al (2017) report an age estimate for GJ 9827.…”
Section: Introductionsupporting
confidence: 90%
“…We find good agreement between our SPECMATCH-EMP derived stellar parameters from the PFS template spectrum and those derived by Niraula et al (2017) and by Houdebine et al (2016) as reported in Rodriguez et al (2017). Our T eff and log g values for GJ 9827 are slightly lower (4085±70 K versus their 4255±110 K and 4270±100 K, 4.67±0.12 cgs versus their 4.70±0.15 cgs and 4.9±0.2 cgs), and our metallicity is Neither Niraula et al (2017) nor Rodriguez et al (2017) report an age estimate for GJ 9827.…”
Section: Introductionsupporting
confidence: 90%
“…Niraula et al (2017) and Teske et al (2018) used SpecMatch-Emp (Yee et al 2017), the results of which are shown in their Table 3 and Table 2 respectively. The stellar parameters used by Rodriguez et al (2018) are shown in their Table 1 and are taken from Houdebine et al (2016), who used principal component analysis.…”
Section: Stellar Parametersmentioning
confidence: 99%
“…Given V and J magnitudes of 9.52 (Zacharias et al 2013) and 5.449±0.027 (Cutri et al 2003) we obtain a mass of 0.36 by also applying the relation of Delfosse et al (2000). According to Houdebine et al (2016) the star has a radius of 0.436±0.049 R ⊙ and effective temperature of 3414±100 K. Neves et al (2012) estimate the metallicity of AD Leo to be [Fe/H] = 0.07 and Royas- Ayala et al (2013) give a value of 0.28±0.17.…”
Section: Ad Leomentioning
confidence: 99%
“…The estimated v sin i of AD Leo is 2.63 kms −1 (Houdebine et al 2016). Together with a radius estimate of 0.436±0.049, Houdebine et al (2016) then calculated a projected rotation period of 8.38 +1.2 −1.1 days.…”
Section: Ad Leomentioning
confidence: 99%
See 1 more Smart Citation